Analisis Yuridis Mengenai Strategi Dosen Terkait Dengan Mutu Pembelajaran Di Perguruan Tinggi Masa Era New Normal - Halimatul Maryani (Universitas Islam Sumatera Utara, 2021)
The scope of education is the parties that are involved in the sphere of education such as proteges/students/college students, the basic and the purpose of education itself, educators, educational materials, educational methods, educational evaluation, educational tools and the surrounding environment within the scope of education. Education is also one of the most important parts of human life that has provisions that aim to help the improvement of living standard and life for themselves and for the country. If referring to the Article 31 (amendment) paragraph (1) of the 1945 Constitution of the Republic of Indonesia which states that